2016
DOI: 10.1186/s12905-016-0314-6
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive method choice among women in slum and non-slum communities in Nairobi, Kenya

Abstract: BackgroundUnderstanding women’s contraceptive method choices is key to enhancing family planning services provision and programming. Currently however, very little research has addressed inter and intra-regional disparities in women’s contraceptive method choice. Using data from slum and non-slum contexts in Nairobi, Kenya, the current study investigates the prevalence of and factors associated with contraceptive method choice among women.MethodsData were from a cross-sectional quantitative study conducted amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
19
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 23 publications
9
19
2
Order By: Relevance
“…This current modern contraceptive utilization is comparable with findings among slum dwellers in Nairobi, Kenya (37.9%), and street beggar women in South Ethiopia (37.4%) [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 80%
“…This current modern contraceptive utilization is comparable with findings among slum dwellers in Nairobi, Kenya (37.9%), and street beggar women in South Ethiopia (37.4%) [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 80%
“…The fact that wealth showed no significant effect on LARC use at any level of the analysis might suggest success in the supply of contraception, as driven by the FP2020 campaign alongside the Ministry of Health, so that issues of cost have been eliminated and LARC is freely available to all potential users [ 38 ]. Previous studies in Kenya have found wealth to positively influence contraception use [ 33 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that women in sub-Saharan Africa are often unable to obtain or use modern contraception, particularly the long acting methods, for many reasons associated with both supply and demand sides[2527]. They rely primarily on traditional and short-acting contraception, which are prone to incorrect or inconsistent use and failure [28, 29].…”
Section: Introductionmentioning
confidence: 99%